Sleep in an At Risk Adolescent Group: A Qualitative Exploration of the Perspectives, Experiences and Needs of Youth Who Have Been Excluded From Mainstream Education - Josie Bainton DEdPsy; Ben Hayes DEdPsy (SAGE Publishing, 2022)
The sleep needs, experiences and viewpoints were explored for UK adolescents who have been excluded from mainstream education. Qualitative data was gathered through interviews with 9 participants, aged 11-15 years, who also completed questionnaires. The participants had symptoms of inadequate sleep, poor sleep hygiene behaviours and were not getting the recommended amount of sleep on school nights. Participants described sleep patterns involving often staying up late and having different sleep timing on weekends than weekdays and having difficulties with their sleep. Use of technology and the relevance of family were identified as important and associated with facilitating and hindering factors for sleep. Participants communicated that they lack control over aspects of their sleep and their lives. The experiences and views of the participants can inform professionals' understanding of how to collaborate with adolescents to improve their sleep and highlight that continued development of sleep education programmes is timely.